2020
DOI: 10.1155/2020/8281741
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Combination of rhBMP-2 with Bone Marrow Aspirate Concentrate in Mandibular Defect Reconstruction after a Pindborg Tumor Resection

Abstract: Recombinant human bone morphogenetic protein-2 (rhBMP-2) is an osteoinductive growth factor used in oral and maxillofacial surgery. It offers a feasible alternative for various regenerative procedures, including reconstruction of mandibular defects. In this study, we report a case of a large Pindborg tumor involving the left mandible. The treatment consisted of surgical resection, followed by off-label use of rhBMP-2 in addition to bone marrow aspirate concentrate, together with an allograft in a titanium mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Using the abovementioned combination, Kamal et al [ 20 ] used titanium mesh for better bond results. Melville et al [ 18 ] in another retrospective study treated 34 cases of tumor-like ameloblastoma, ossifying fibroma, odontogenic keratocyst (OKC), etc., using a non-resorbable titanium mesh or resorbable poly(L-lactide) (PLLA) or poly(D, L-lactide) (PDLLA) membrane addition of the mentioned combination bond, it was found that the graft is exceptionally vulnerable to bacterial contamination and also any patients with a history of uncontrolled health disease, chemotherapy, or radiation therapy negatively affect the graft’s viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the abovementioned combination, Kamal et al [ 20 ] used titanium mesh for better bond results. Melville et al [ 18 ] in another retrospective study treated 34 cases of tumor-like ameloblastoma, ossifying fibroma, odontogenic keratocyst (OKC), etc., using a non-resorbable titanium mesh or resorbable poly(L-lactide) (PLLA) or poly(D, L-lactide) (PDLLA) membrane addition of the mentioned combination bond, it was found that the graft is exceptionally vulnerable to bacterial contamination and also any patients with a history of uncontrolled health disease, chemotherapy, or radiation therapy negatively affect the graft’s viability.…”
Section: Resultsmentioning
confidence: 99%
“…Successful reconstruction with a reasonably high long-term success rate (up to 70%) has been achieved with autogenous bone grafts. For decades, autografts as a natural biomaterial have been considered the gold standard due to superior osteoinductivity, osteoconductivity, and osteogenesis, compared with other types of materials [ 20 , 33 ]. Osteo-cutaneous free flaps, especially fibula free flaps, are the most common autografts used for crucial-sized grafts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Col mats’ mechanical properties and osteoinductivity have been enhanced by adding calcium phosphate (CaP) or apatite by in vitro mineralization. Interestingly, mineralized Col scaffolds accelerated bone regrowth in large CMF defects in rats, rabbits, and sheep after implantation. Clinically, various Col sponges have been authorized by the US Food and Drug Administration (FDA) for CMF applications. , …”
Section: Biomaterials Employed To Fabricate Scaffolds Suitable For Cm...mentioning
confidence: 99%
“…28−30 Clinically, various Col sponges have been authorized by the US Food and Drug Administration (FDA) for CMF applications. 31,32 Gel has been tested for CMF applications, mainly as hydrogels. Gel methacryloyl (GelMA) hydrogel scaffolds, functionalized with a growth factor and a peptide, accelerated bone regrowth in rat cranial CSDs.…”
Section: Natural Polymersmentioning
confidence: 99%
“…It can be used to promote fracture repair, but it has the disadvantages of being easily diluted by body fluids and short half-life in inducing bone formation in the body, which reduces the osteogenesis ability (11). Using polymer materials to embed cytokines for the slow release can make the drug release slowly and maintain the local effective drug stimulation concentration (12).…”
Section: Introductionmentioning
confidence: 99%